Secular Stagnation: A Supply-Side View - Gordon, Robert J. (American Economic Review, 2015)
Secular stagnation on the supply side takes the form of a slow 1.6 percent annual growth rate of US potential real GDP, roughly half the 3.1 percent annual growth rate of actual real GDP realized from 1972 to 2004. This slowdown stems from a sharp decline in the growth rate of aggregate hours of work and of output per hour. This paper attributes the productivity growth decline to diminishing returns in the digital revolution that had its peak effect business hardware, software, and best practices in the late 1990s but has resulted in little change in those methods over the past decade.